The Role of the Principal in Improving Early Childhood Teachers’ Professional Competence - Yanti, Fitri; Haryati, Titik; Abdullah, Ghufron (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to explore in depth the experiences and perspectives of school principals in fulfilling their roles to enhance the quality of education at Taman Kanak-Kanak Taman Indriya (Taman Indriya Kindergarten), Boja Subdistrict, Kendal Regency. This research employs a qualitative approach with a phenomenological design, focusing on the subjective meaning of participants' lived experiences. The data used in this study consist of the principals’ and teachers’ narratives obtained through in-depth interviews, observational field notes recorded during school activities, and relevant documents such as school programs, supervision notes, and teacher activity records. The data were analyzed using a phenomenological analysis technique following the stages of data reduction, coding, theme development, and meaning interpretation based on the lived experiences of participants. Through this process, the findings reveal that the principal perceives her role as a manager in designing and organizing programs participatively, as a leader who fosters positive relationships and work motivation, and as an innovator who develops contextual learning and promotes active parental involvement. These three roles are carried out reflectively and adaptively in response to the institution’s challenges and needs. This study underscores the importance of a humanistic and contextual leadership approach in managing early childhood education. The findings have implications for strengthening the leadership capacity of ECE principals based on a deep understanding of real-world contexts and lived experiences.